The State of the Power Sector in Rwanda: A Progressive Sector With Ambitious Targets - Bimenyimana, Samuel; Asemota, Godwin N. O.; Li, Lingling (Frontiers in Energy Research, 2018)
The Government of Rwanda through its power sector has very ambitious targets to achieve 512 MW installed power generation capacity, from its current 216 MW power generation and have universal access (100%) by 2023/24. It is also determined to achieve 52% on-grid connections and 48% off-grid connections by 2023/24. Literature review, analyses, and site visits to various branch offices of the Rwanda Energy Group (REG) were used to evaluate and determine the success of the power sector in achieving its goals, targets and aspirations. Also, hydropower has a high generation percentage (46.8%), because it has longer plant life, higher capacity factor and availability, numerous rivers coupled with Rwanda embarking upon upgrade and vigorous expansion programmes. Furthermore, the potential to generate electricity economically with local resources including, hydropower, peat, lake gas methane and geothermal energy has however, been estimated to total around 1613 MW. The country is therefore, utilising less than 10% of its local electricity potential, excluding a substantial solar resource, while incurring a large foreign outflow. The Rwanda’s electricity tariff was estimated to be about 22.2% more expensive, compared to the highest electricity tariff of other East African Community (EAC) countries. The reports of Electricity Access Roll-out Programme (EARP) also show that the number of new customer connections increased from 364,000 households in June 2012 to more than 700,000 households (31% of the total households in Rwanda) in 2017.